Generation of Novel Severe Acute Respiratory Syndrome Coronavirus 2 Variants on the B.1.1.7 Lineage in 3 Patients With Advanced Human Immunodeficiency Virus-1 Disease. (25th May 2022) - Riddell, Anna C; Kele, Beatrix; Harris, Kathryn; Bible, Jon; Murphy, Maurice; Dakshina, Subathira; Storey, Nathaniel; Owoyemi, Dola; Pade, Corinna; Gibbons, Joseph M; Harrington, David; Alexander, Eliza; et al.
Abstract: The emergence of new severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants is of public health concern in case of vaccine escape. Described are 3 patients with advanced human immunodeficiency virus (HIV)-1 and chronic SARS-CoV-2 infection in whom there is evidence of selection and persistence of novel mutations that are associated with increased transmissibility and immune escape.